A Study of Bluetooth Application for Remote Controlling of Mobile Embedded Systems - Silva, J. F. M. C.; Santos, D. M. S.; Marques, V. C.; Oliveira, K. D.; Rodrigues, T. O.; Texeira, R. G. F.; Menezes, J. W. M.; Silva, F. D. (Anais do Simpósio Brasileiro de Engenharia de Sistemas Computacionais (SBESC); 2012: Anais do II Simpósio Brasileiro de Engenharia de Sistemas Computacionais, 2012)
This paper presents the development of an application for the operational system Android (Android OS) with the intent of controlling embedded systems via Bluetooth. The system to be operated is a teleoperated vehicle for remote sensoring and environmental damage detection. This prototype remotecontrolled vehicle was developed using the open-source development platform Arduino. This prototype has three wireless communication modules: one for Bluetooth communication, another for Zigbee communication, and the last one is a infra-red signal receiver. The results in laboratory tests and in real application field showed the prototype was successful, referring to its initial objectives, controlling locomotion system and high level human-machine interface.